Mediatized World in Digital Music Industry: Transformations, Challenges, and Opportunities - A Study in Indonesia - Akil, Roxanne; Rasyidin, Nikita; Lumongga Dwihadiah, Desideria (PT Mattawang Mediatama Solution, 2024)
The world of music industry has experienced profound transformation in recent years due to digital revolution. This research explores the changes, challenges, and opportunities in the digital music industry. From the evolution of production to distribution, the researcher analyzed this dynamics industry. Several challenges, such as piracy and unequal revenue distribution are faced, yet opportunities arise through digital platforms and blockchain technology. Collaboration between governments, copyright organizations and artists become the key to creating a sustainable music ecosystem. As such, the research not only reflects the essence of the title, but also provides deep insights into how mediatization can be implemented to understand the transformation of the digital music industry in Indonesia, as well as the related challenges and opportunities.